MPSJ forms green partnership with university. - New Straits Times, (2011)
SUBANG JAYA: Subang Jaya Municipal Council(MPSJ) has signed a memorandum of understanding (MoU) with Universiti Putra Malaysia(UPM)to carry out a research and development programme in thr field of forestry here,recently.